Simultaneous Analysis of 6-Mercaptopurine, 6-Methylmercaptopurine, and 6-Thioguanosine-5’-monophosphate in Dried Blood Spot Using Ultra Performance Liquid Chromatography Tandem Mass Spectrometry - Supandi Supandi; Yahdiana Harahap; Harmita Harmita; Rizka Andalusia (Universitas Gadjah Mada, 2018)
6-Mercaptopurine is a chemotherapeutic agent of the antimetabolite class. This study aims to analyze simultaneous validation of 6-mercaptopurine (6-MP), 6-methylmercaptopurine (6-MMP), and 6-thioguanosine-5’-monophosphate (6-TGMP) in dried blood spot (DBS) using ultra performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS). An accurate volume of 60 μL blood was spotted onto DBS-CAMAG paper and then extracted using methanol 90% (v/v) containing an internal standard of 5-fluorouracil (5-FU). Separation was performed using a Waters Acquity UPLC BEH AMIDA column 1.7 μm (2.1 x 100 mm) with a mobile phase mixture of 0.2% (v/v) formic acid in water−0.1% (v/v) formic acid in acetonitrile-methanol with gradient elution and flow rate of 0.2 mL/min. Mass detection was done using Waters Xevo TQD with positive electrospray ionization (ESI) for 6-MP, 6-MMP, 6-TGMP and negative ESI for 5-FU, in multiple reaction monitoring mode. Detection rates of 6-MP, 6-MMP, 6-TGMP and 5-FU were m/z 153.09 > 119.09; 167.17 > 126.03; 380.16 > 168.00); 129.09 > 42.05, respectively. This method is linear across the range 25.5–1020 ng/mL for 6-MP, 6-MMP and 6-TGMP. This method is valid for the in vitro simultaneous analysis of 6-MP, 6-MMP and 6-TGMP in DBS, based on European Medicine Agency guidelines.